Possibilities of second order difference plot features for differentiation of low back pain by electromyographic signals - Hamdiya Alhassan (ХНУРЕ, 2023)
This study explores the potential of second-order difference plot (SODP) features for differentiating low back pain using electromyographic (EMG) signals. The SODP features were found to exhibit significant differences between patients with low back pain and healthy individuals. The dynamics of these features were also consistent across different segments of the EMG signal, suggesting their potential as reliable indicators for diagnosis. Overall, SODP features offer a promising approach for differentiating low back pain using EMG signals, with potential for clinical use pending further validation.
Keywords: EMG signals; peak amplitude; muscle activation